Human primary keratinocytes show restricted ability to up-regulate suppressor of cytokine signaling (SOCS)3 protein compared with autologous macrophages - Zeitvogel, Jana; Dalpke, Alexander (The journal of biological chemistry, 2012)
Suppressor of cytokine signaling (SOCS)3 belongs to a family of proteins that are known to exert important functions as inducible feedback inhibitors and are crucial for the balance of immune responses. There is evidence for a deregulated immune response in chronic inflammatory skin diseases. Thus, it was the aim of this study to investigate the regulation of SOCS proteins involved in intracellular signaling pathways occurring during inflammatory skin diseases and analyze their impact on the course of inflammatory responses. Because we and others have previously described that the cytokine IL-27 has an important impact on the chronic manifestation of inflammatory skin diseases, we focused here on the signaling induced by IL-27 in human primary keratinocytes compared with autologous blood-derived macrophages. Here, we demonstrate that SOCS3 is critically involved in regulating the cell-specific response to IL-27. SOCS3 was found to be significantly up-regulated by IL-27 in macrophages but not in keratinocytes. Other STAT3-activating cytokines investigated, including IL-6, IL-22, and oncostatin M, also failed to up-regulate SOCS3 in keratinocytes. Lack of SOCS3 up-regulation in skin epithelial cells was accompanied by prolonged STAT1 and STAT3 phosphorylation and enhanced CXCL10 production upon IL-27 stimulation compared with macrophages. Overexpression of SOCS3 in keratinocytes significantly diminished this enhanced CXCL10 production in response to IL-27. We conclude from our data that keratinocytes have a cell type-specific impaired capacity to up-regulate SOCS3 which may crucially determine the course of chronic inflammatory skin diseases.
Gesehen am 24.07.2018